Legal Protection for Victims of Sexual Harassment Crimes in The Law Enforcement Process by The Asahan Resort Police - Eben Heser Tarigan; Suci Ramadani; Rahmyanti Rahmyanti (Journal Evidence Of Law, 2026)
This study discusses the urgency of implementing legal protection for victims of sexual abuse in the law enforcement process by the Asahan Resort Police. Sexual abuse cases are a form of violation of human dignity that often causes physical and psychological suffering for victims. In practice, many victims do not receive maximum legal protection due to the weak implementation of laws and regulations, the low sensitivity of law enforcement officials, and the still strong patriarchal culture in society. The purpose of this study is to analyze the importance of legal protection for victims of sexual abuse and to examine the role and responsibilities of the police in ensuring justice for victims at the regional level, particularly in the jurisdiction of the Asahan Resort Police. The research method used is a normative juridical approach by examining various laws and regulations such as Law Number 12 of 2022 concerning Sexual Violence Crimes (TPKS Law), Law Number 31 of 2014 concerning Witness and Victim Protection, and internal regulations of the Indonesian National Police. The results of the study show that the application of legal protection for victims of sexual abuse is of high urgency in realizing a sense of justice and preventing victims from being revictimized. The Asahan Police Resort has a strategic role as the front line in the law enforcement process, so it is necessary to increase the capacity of the apparatus, apply victim-oriented procedures, and collaborate with victim assistance institutions such as the LPSK and DP3A. In conclusion, the effective implementation of legal protection for victims of sexual abuse is not only a legal obligation, but also a form of respect for human rights and gender justice. Through a humane law enforcement mechanism that is sensitive to victims and in accordance with the principles of substantive justice, it is hoped that the Asahan Resort Police can set an example of the implementation of legal protection that favors victims and strengthens public trust in the criminal justice system in Indonesia